The Value of the Legal Standards on Labor - Tat'yana M. Ponomareva (Сибирское юридическое обозрение, 2017)
The purpose of the Author's research is to find the patterns of development of labor legislation in Russia in the period of the 19th-20th centuries. The scientific and practical significance of the research is the formulation of legal problems of legal regulation in the field of labor relations , taking into account the analysis of modern practice of local regulation and judicial acts. The methodology of the study includes a systematic approach and comparative-historical analysis. The Author comes to the conclusion that the evolution of Russian labor law is a continuous search for an optimal balance of interests of the employee, employer and the state against the background of changing historical conditions. As a result of the study, conclusions were also drawn about the general formalization of labor legislation, the lack of control in this sphere, the need for the parties of labor relations to strive for balance of interests.